2003
DOI: 10.1016/s0895-7061(03)00006-2
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride reduces stroke and renalinjury in stroke-prone hypertensive rats

Abstract: These findings suggest that interference with sodium channel function, perhaps at sites other than the kidney epithelium, may play a role in protecting against the evolution of cerebral and renal vascular injury in saline-drinking SHRSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Does this organ saving effect of amiloride depend on the antihypertensive effect? In previous animal studies where amiloride and salt were given to deoxycorticosterone acetate treated rats and stroke-prone spontaneously hypertensive rats, amiloride improved cardiac fibrosis and decreased urinary protein excretion despite the facts that it did not decrease BP, affect serum potassium levels, or urinary electrolytes [40,41]. Additionally, where amiloride was given to uninephrectomized aldosterone-salt treated rat, it lowered elevated BP and attenuated myocardical fibrosis not only in left but also in right ventricle.…”
Section: Discussionmentioning
confidence: 96%
“…Does this organ saving effect of amiloride depend on the antihypertensive effect? In previous animal studies where amiloride and salt were given to deoxycorticosterone acetate treated rats and stroke-prone spontaneously hypertensive rats, amiloride improved cardiac fibrosis and decreased urinary protein excretion despite the facts that it did not decrease BP, affect serum potassium levels, or urinary electrolytes [40,41]. Additionally, where amiloride was given to uninephrectomized aldosterone-salt treated rat, it lowered elevated BP and attenuated myocardical fibrosis not only in left but also in right ventricle.…”
Section: Discussionmentioning
confidence: 96%
“…Radiotelemetry probes (TA11PA-C40; Data Sciences International, St. Paul, MN) were implanted using sterile techniques in rats anesthetized with sodium pentobarbital (50 mg/kg, ip; Abbott Laboratories, North Chicago, IL) as previously described [2628]. Briefly, a midline abdominal incision was made and the telemetry probe catheter was introduced retrogradely into the descending aorta through a puncture site which was then sealed with tissue adhesive (3M Vetbond 1469, 3M Animal Care Products, St. Paul, MN).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a 1961 publication a trial comparing prednisolone, placebo and calcium aspirin, reported no deterioration in patients on aspirin, whereas there was clear clinical worsening in the other two groups . Moreover, antihypertensive drugs with a protective effect on cerebrovascular disease, such as amiloride , may exert a neuroprotective effect in progressive MS . Finally, biotin, an important cofactor for many mitochondrial enzymes that protects against hypoxia associated energy failure may reverse disability in progressive MS .…”
Section: Ms and Svd: Evidence For A Possible Interactionmentioning
confidence: 99%